Adapting to Learning Services During Covid-19: A Risk Mitigation Review - Aziz, Reva Abdul; Nurannisa, Anti (JURNAL AL-TANZIM, 2022)
The purpose of this study was to analyze online learning during the COVID-19 pandemic and its solutions at SDIT Insan Rahayu Rancaekek Bandung. This research uses a qualitative approach with a case study type, the data obtained through interviews, observation, and documentation. This study indicates that the implementation of online learning during the covid-19 pandemic has problems for teachers: weak mastery of information technology devices and limited access to student supervision. Students have problems related to the inactivity of students in participating in learning, limited supporting facilities, and internet network access. Meanwhile, parents have limited time to accompany their children during online learning. These problems can be overcome by increasing the competence of teachers' IT mastery as well as intensive supervision involving the role of parents who are also supervised by the school so that two important roles involved in children's education as well as on the side of assignments that are carried out manually can be completed without any problems.